Clinical manifestations and outcomes of coronavirus disease‐19 in heart transplant recipients: a multicentre case series with a systematic review and meta‐analysis. (5th March 2021) - Granger, Camille; Guedeney, Paul; Arnaud, Camille; Guendouz, Soulef; Cimadevilla, Claire; Kerneis, Mathieu; Kerneis, Caroline; Zeitouni, Michel; Verdonk, Constance; Legeai, Camille; Lebreton, Guillaume; Leprince, Pascal; et al.
Summary: Available data on clinical presentation and mortality of coronavirus disease‐2019 (COVID‐19) in heart transplant (HT) recipients remain limited. We report a case series of laboratory‐confirmed COVID‐19 in 39 HT recipients from 3 French heart transplant centres (mean age 54.4 ± 14.8 years; 66.7% males). Hospital admission was required for 35 (89.7%) cases including 14/39 (35.9%) cases being admitted in intensive care unit. Immunosuppressive medications were reduced or discontinued in 74.4% of the patients. After a median follow‐up of 54 (19–80) days, death and death or need for mechanical ventilation occurred in 25.6% and 33.3% of patients, respectively. Elevated C‐reactive protein and lung involvement ≥50% on chest computed tomography (CT) at admission were associated with an increased risk of death or need for mechanical ventilation. Mortality rate from March to June in the entire 3‐centre HT recipient cohort was 56% higher in 2020 compared to the time‐matched 2019 cohort (2% vs. 1.28%, P = 0.15). In a meta‐analysis including 4 studies, pre‐existing diabetes mellitus (OR 3.60, 95% CI 1.43–9.06, I 2 = 0%, P = 0.006) and chronic kidney disease stage III or higher (OR 3.79, 95% CI 1.39–10.31, I 2 = 0%, P = 0.009) were associated with increased mortality. These findings highlight the aggressive clinical course of COVID‐19 in HT recipients.